Pengaruh Edukasi Postpartum terhadap Kemampuan Perawatan Bayi dan Pemberian ASI Eksklusif pada Ibu Primipara Post Sectio Caesarea di Rumah Sakit Efarina Etaham Pematang Siantar - Santi Widya Purba; Siti Nurul Fadhilah Sari; Renta Sihombing (Yayasan Literasi Sains Indonesia, 2026)
The postpartum period is a critical time for mothers to adapt to their new roles, especially for primiparous mothers who have undergone delivery through a caesarean section (CS). Postoperative conditions often lead to limited mobility and pain, which can affect a mother’s ability to care for her baby and provide exclusive breastfeeding. One effective intervention that can help mothers during this transitional period is comprehensive postpartum education. This study aims to determine the effect of postpartum education on baby care ability and exclusive breastfeeding among primiparous mothers post caesarean section at Efarina Etaham Hospital, Pematang Siantar. The research design used was a quasi-experimental approach with a pre-test and post-test control group design. The sample consisted of primiparous mothers post-CS who met the inclusion criteria, selected through purposive sampling. Research instruments included a baby care ability observation sheet and a questionnaire on exclusive breastfeeding practices. Data analysis was conducted using paired t-tests and independent t-tests to determine differences in ability before and after education. The results showed a significant improvement in baby care ability and exclusive breastfeeding practices after postpartum education was provided (p < 0.05). Therefore, it can be concluded that postpartum education has a positive effect on improving the ability of primiparous mothers post caesarean section in baby care and exclusive breastfeeding.